Multidimensional performance enablers of Ethiopian community-based health extension program: A scoping review - Kora Tushune Godana; Zewdie Birhanu; Gugsa Nemera; Kasahun Eba; Fikadu Balcha; Yibeltal Assefa; Wim V. Damme; Peter Decat (PLoS ONE, 2025)
Introduction Ethiopian Health Extension Program (HEP) aims to improve access to primary care, yet suboptimal health outcomes persist, indicating the need to optimize HEP implementation. This scoping review aims is to identify and synthesize evidence on the enabling factors that influence the Ethiopian HEP and Health Extension Workers (HEWs) performance. Methods A comprehensive search strategy was employed across multiple databases, including PubMed, EMBASE, Web of Science, and institutional websites. The review included studies published since January 2003, encompassing quantitative, qualitative, and mixed-methods researchs. The PRISMA flow diagram guideline was utilized for reporting of a review process and JBI methodology guideline was used for data extraction. Data extraction was conducted using Atlas.ti software, capturing verbatim excerpts and applying thematic coding to illustrate key findings. Results This review identified key multidimensional enablers of the Ethiopian HEP that collectively enhance the program’s performance. Motivational factors for HEWs play a critical role, encompassing intrinsic desires and extrinsic factors including opportunities for career growth and fair compensation. Additionally, the review identified the importance of continuous capacity building to enhance the skills of HEWs and program performance. The review also highlights the positive impact of diversifying HEP services including customizing the HEP services to the varied contexts and integrating male HEWs to enhance program reach and acceptance. Engaging communities through organized campaigns, stakeholder coordination, and leveraging local structures enable and strengthen the program’s effectiveness. Finally, the availability of essential resources is crucial for HEWs to provide timely and appropriate care. These multidimensional enabling factors form pathways for HEWs and HEP to create supportive environment and capability that significantly enhances HEP performance. Conclusions Intrinsic and extrinsic motivations, community engagement, clinical nurse inclusion, male HEWs participation, mentorship and improving living conditions of HEWs enhances the HEWs’ effectiveness and program performance.